2021
DOI: 10.1371/journal.pone.0247917
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of circulating microRNA-107 are elevated in patients with early-stage HCC

Abstract: Background Early detection of hepatocellular carcinoma (HCC), the most common primary liver malignancy, is crucial to offer patients a potentially curative treatment strategy such as surgical resection or liver transplantation (LT). However, easily accessible biomarkers facilitating an early diagnosis of HCC as well as a reliable risk prediction are currently missing. The microRNA(miR)-107 has recently been described as a driver of HCC in both murine and human HCC but data on circulating miR-107 in HCC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Nagi et al, 2018 reported that five miRNAs from 173 (miRNA 584, miRNA 31, miRNA 146b-3p, miRNA 105, and miRNA 29c) showed the best performing related to prognosis value based on multivariate survival analysis [ 48 ]. The median overall survival (OS) HCC subject of the study was 54 days (range: 2–851, days) was lower than the recent study by Ali et al, 2018 (median 10.7 months; range: 9.5–12.9 months) and research by Loosen et al, 2021 (high expression was 83.24 months and 48.99 months low expression) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 56%
“…Nagi et al, 2018 reported that five miRNAs from 173 (miRNA 584, miRNA 31, miRNA 146b-3p, miRNA 105, and miRNA 29c) showed the best performing related to prognosis value based on multivariate survival analysis [ 48 ]. The median overall survival (OS) HCC subject of the study was 54 days (range: 2–851, days) was lower than the recent study by Ali et al, 2018 (median 10.7 months; range: 9.5–12.9 months) and research by Loosen et al, 2021 (high expression was 83.24 months and 48.99 months low expression) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 56%
“…Despite its attractive characteristics, circulating miRNAs was rarely investigated in LT, with a total of four studies: two focusing on LT ( 36 , 37 ) ( Table 2 ) and two studies also including other treatments ( 42 , 43 ).…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…[ 34 , 35 ] Serum chromogranin A and microRNA-107 expression levels could be potential diagnostic markers in early stage HCC. [ 36 , 37 ] Deng et al [ 38 ] found that serum pentraxin 3 was an independent risk factor of HCC and could identify hepatitis B virus-associated HCC with an AUC of 0.920 for early-stage HCC. However, further studies are needed to confirm these potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%